Precursors for p‐Type Nickel Oxide: Atmospheric‐Pressure Metal–Organic Chemical‐Vapour Deposition (MOCVD) of Nickel Oxide Thin Films with High Work Functions. Issue 13 (3rd April 2017) - Cosham, Samuel D.; Richards, Stephen P.; Manning, Troy; Hill, Michael S.; Johnson, Andrew L.; Molloy, Kieran C.
Abstract : A series of unsymmetrical nickel β‐diketonate derivatives have been synthesised and structurally characterised for application as atmospheric‐pressure metal–organic chemical vapour deposition (AP‐MOCVD) precursors for nickel oxide. (TMEDA)Ni[MeC(O)CHC(O)OEt]2 (TMEDA = tetramethylethylenediamine) was selected and used to deposit NiO films of varying thickness onto commercial indium tin oxide (ITO)‐coated glass; the work function of the ITO was raised as a consequence. Abstract : We describe a series of nickel(II) β‐diketonate precursors and their use in the atmospheric‐pressure chemical‐vapour deposition of very thin films of NiO on indium tin oxide (ITO) at 400 °C. Auger spectroscopy revealed that the as‐deposited films are rich in Ni metal, which is partially transformed to NiO on annealing, and showed a significant modification of the work function of the ITO.